Strength Enhancement, Ductility, and Confinement Effectiveness Index of Fly Ash-based Geopolymer Concrete Square Columns - Herwani Herwani; Iswandi Imran; Bambang Budiono; Ediansjah Zulkifli (Institute for Research and Community Services, Institut Teknologi Bandung, 2022)
Geopolymer concrete is an environmentally friendly construction material that has the potential to be applied in building structures. It is important to understand the structural behavior of geopolymer concrete. This paper presents an experimental investigation into the performance of structural elements of geopolymer concrete under concentric axial loads. The specimens were twelve square columns with a size of 170 x 170 mm and a height of 480 mm. The study variables were the tie spacing and the compressive strength of unconfined geopolymer concrete (f’c). The test results showed that the increase in f'cc was not as significant as the increase in unconfined concrete compressive strength (f'c). The value of strength enhancement (K) tended to decrease. The column ductility (m) and confinement effectiveness index (Ic) had optimum values. The effect of increasing the tie spacing (s) decreased the K, Ic, and m values of the column. The proposed f’cc formulation for geopolymer concrete is compatible.